MINERALS, VITAMINS, AND ANTINUTRITIONAL CONTENTS OF MAIZE OGI ENRICHED WITH AFRICAN YAM BEAN (Sphenostylis stenocarpa) SOY FLOURS (Glycine max) AND THEIR PROTEIN ISOLATES - Ochelle, Paul, O.; Sogunle, K. Atanda (FUDMA JOURNAL OF SCIENCES, 2026)
Ogi is a traditional fermented cereal gruel produced from cereals. Its nutritional qualities were improved with enrichment with flours and protein isolates from African yam bean and soy bean, while antinutritional factors decreased. Material balance was used in formulation to attain 16% protein dry weight. Sample B contained 53.40% maize ogi and 46.60% African yam bean flour; Sample C contained 76.40% maize ogi and 23.40% soy flour; Sample D contained 89.40% maize ogi and 10.60% African yam bean protein isolate; and Sample E contained 90.20% maize ogi and 9.80% soy protein isolate. Standard laboratory procedures were used for all analyses. Enrichment significantly altered results (p≤0.05). Mineral and vitamin contents of maize ogi increased significantly following enrichment. Calcium rose from 56.03 mg/100g in Sample A to 170.95 mg/100g in Sample C. Phosphorus increased from 154.76 to 271.74 mg/100g. Sodium rose from 8.00 to 44.26 mg/100g, and potassium from 178.20 to 449.74 mg/100g. Thiamine levels increased from 0.51 to 0.96 mg/100g. Riboflavin rose from 0.27 to 0.57 mg/100g, and niacin from 1.97 to 2.70 mg/100g.Antinutritional factors also showed significant differences (p≤0.05). Phytate increased from 2.57 to 9.48 mg/100g, oxalate from 0.22 to 5.05 mg/100g in Sample B, tannins from 0.34 to 7.57 mg/100g, and trypsin inhibitor activity from 0.46 to 10.59 mg/100g. Protein isolate samples D and E recorded lower antinutritional values. Overall, addition of African yam bean, soy flours, and their protein isolates to maize ogi reduced antinutritional contents to tolerable levels while increased mineral and vitamin contents.
Keywords: Malnutrition; African yam bean flour; Soy Flour; Protein Isolates; maize ogi; vitamin contents; mineral content; antinutritional contents